2 - The Invisible Cohesion of African Leadership: The Lead Up to the 1819 Battle at Grahamstown Reconsidered - Julia C. Wells (Afrika Zamani, 2022)
Historians are often troubled by the need to account for the ways that disunity among African leaders helped to pave the way for colonial conquest. In the Eastern Cape of South Africa, the success of the British in conquering territory belonging to the Xhosa people has been frequently attributed to a bitter power struggle between King Ngqika and his uncle Chief Ndlambe of the Rharhabe nation. From the first arrival of the British in the area in 1798, the newly- inaugurated Ngqika tried to enlist their help to counter the influence of his uncle, who had recently handed over the reins of power after a long regency. Over the next 20 years, the two leaders went to battle against each other on three occasions. The ultimate massive defeat of a large Xhosa force of up to 10,000 men at the battle of Grahamstown in 1819 has been identified as the turning point of Xhosa power, confirming the high price to be paid for royal rivalries. This article, however, identifies a concurrent trend towards cooperation between the two Chiefs, which has gone unrecognised. It argues that through the tumultuous twenty years of trying to come to terms with the implications of the British presence, the younger chief came to understand the greater imperative of unity in the face of a dangerous enemy. A starting point is the insight of Xhosa informal historians which claims that the conflicts between the Chiefs had more of a character of disciplining and enforcing traditional leadership values, than of a rivalry for the sole domination of one over the other. Using oral traditions, archival sources and translations from texts written in the Xhosa language, the seldom-appreciated spirit of building the nation is traced.